Upaya Meningkatkan Prestasi Belajar IPA melalui Model Pembelajaran Kooperatif Tipe Group Investigation pada Siswa Kelas V MIN Semanu Gunungkidul - Wahidin Wahidin (Jurnal Pendidikan Madrasah, 2018)
This study aims to determine the effort to improve the achievement of natural science learning through cooperative learning model type Investigation Group in grade V students in MIN Semanu Gunungkidul Regency School year 2013/2014. This research is a classroom action research. The subjects of this study were all students of class V MIN Semanu Gunungkidul Regency which amounted to 18 students consisting of 7 male students and 11 female students. The object of this research is the Group Investigation model. The steps of the TOD include planning, implementation, observation, test and documentation. The results of this study can be concluded that: (1) the use of Group Investigation model can improve students' learning achievement of IPA. The average value in class V MIN Semanu of Gunungkidul Regency at precycle equal to 68,89 with learn 55,56% completeness with enough criterion. After implemented the study with Group Investigation model increased in the first cycle average score became 74.28 with mastery learning of 72.22 including high criteria. In cycle II the average score becomes 76,72 with learning completeness 88,89 including very high criterion. (2) an increase in the implementation of learning processes and students. From the data, it can be concluded that the application of Group Investigation model can improve the learning achievement of science in grade V students Semanu Gunungkidul.